2000
DOI: 10.4049/jimmunol.164.5.2815
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Significance of Anti-Latent Membrane Protein-1 Antibodies in the Sera of Patients with EBV-Associated Diseases

Abstract: Anti-latent membrane protein-1 (LMP-1) is an EBV-encoded type III integral membrane protein with oncogenic potential that is expressed most consistently in various EBV-associated malignancies. Unlike many other EBV proteins, LMP-1 Abs have rarely been demonstrated in EBV-associated disease conditions. We established a high level LMP-1-expressing cell clone and used it for the detection, quantitation, and characterization of these Abs in various human sera in immunoblots and ELISA. Our results demonstrate that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 53 publications
(44 reference statements)
4
39
0
Order By: Relevance
“…25 In our view, therefore, sequence divergence is unlikely to have led to a significant underestimate of LMP-specific immunity. The present data indicating that the LMPs are only weakly immunogenic accord with the finding that the LMPs only induce detectable humoral responses in rare circumstances; thus anti-LMP1 antibodies have been detected in a subset of patients with HD or NPC but not in most healthy carriers, 23,31,32 while anti-LMP2 antibodies have only been described in NPC patients. 23,33,34 Furthermore, our recent studies have shown that LMP1 and LMP2 are also a poor source of epitopes for the CD4 ϩ T cell response.…”
Section: Discussionsupporting
confidence: 88%
“…25 In our view, therefore, sequence divergence is unlikely to have led to a significant underestimate of LMP-specific immunity. The present data indicating that the LMPs are only weakly immunogenic accord with the finding that the LMPs only induce detectable humoral responses in rare circumstances; thus anti-LMP1 antibodies have been detected in a subset of patients with HD or NPC but not in most healthy carriers, 23,31,32 while anti-LMP2 antibodies have only been described in NPC patients. 23,33,34 Furthermore, our recent studies have shown that LMP1 and LMP2 are also a poor source of epitopes for the CD4 ϩ T cell response.…”
Section: Discussionsupporting
confidence: 88%
“…Using a more sensitive RT-PCR-based detection, several reports revealed much higher frequencies (>80%) of LMP1 expression (47,48). In addition, >70% of NPC patients' sera are positive for anti-LMP1 (49). Taken together, the positive rate for LMP1 in NPC is likely underestimated due to the sensitivity and specificity of the detection method.…”
Section: Discussionmentioning
confidence: 94%
“…Establishment and characterization of the HDE-14 LCL have been described elsewhere (Pomponi et al, 1996). BJAB cells transfected with the pIgLMP-1 plasmid and the vector alone (Xu et al, 2000) were kindly provided by Dr J Meneze´s (University of Montreal, Canada). Cell lines were cultured in RPMI 1640 supplemented with 10% heat-inactivated fetal calf serum, 100 U/ml penicillin, 100 mg/ml streptomycin, and 20 mm l-glutamine, and maintained in a humidified 5% CO 2 incubator at 371C.…”
Section: Cell Lines Patient Samples and Culture Conditionsmentioning
confidence: 99%